2022
DOI: 10.1021/jacs.1c11900
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of the Xenon–Protein Interactome Using Large-Scale Measurements of Protein Folding and Stability

Abstract: The intermolecular interactions of noble gases in biological systems are associated with numerous biochemical responses, including apoptosis, inflammation, anesthesia, analgesia, and neuroprotection. The molecular modes of action underlying these responses are largely unknown. This is in large part due to the limited experimental techniques to study protein–gas interactions. The few techniques that are amenable to such studies are relatively low-throughput and require large amounts of purified proteins. Thus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 70 publications
0
11
0
Order By: Relevance
“…H 2 O 2 was selected as the oxidant due to its relative ease of use, availability, and reported oxidizing capability in a protein context. 29,30 A publication that reports the addition of azido radicals to free tryptophan suggests that the adduct reaction is inefficient and produces a product with relatively low abundance. 17 Thus, we developed an assay to detect and enrich the modified compound via click chemistry (CuAAC).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…H 2 O 2 was selected as the oxidant due to its relative ease of use, availability, and reported oxidizing capability in a protein context. 29,30 A publication that reports the addition of azido radicals to free tryptophan suggests that the adduct reaction is inefficient and produces a product with relatively low abundance. 17 Thus, we developed an assay to detect and enrich the modified compound via click chemistry (CuAAC).…”
Section: Resultsmentioning
confidence: 99%
“…Classically, azido radicals that interact with free amino acids are generated by linear particle accelerators irradiating water to create hydroxyl radicals, which in turn react with azide to produce azido radicals. , Given this, we asked whether more accessible methods of oxidation could facilitate azido radical generation in a physiological buffer system. H 2 O 2 was selected as the oxidant due to its relative ease of use, availability, and reported oxidizing capability in a protein context. , A publication that reports the addition of azido radicals to free tryptophan suggests that the adduct reaction is inefficient and produces a product with relatively low abundance . Thus, we developed an assay to detect and enrich the modified compound via click chemistry (CuAAC) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SPROX is the most mature of the technologies used for characterizing protein structure proteome-wide, having been applied to numerous systems over the course of many years, and benchmarked against alternative technologies. [126][127][128][129][130] SPROX is well-validated for providing reliable unfolding free energies for at least proteins that follow twostate unfolding models. Even for proteins that defy two-state transitions, oxidation kinetics are a valid proxy for destabilization.…”
Section: Footprinting Methodsmentioning
confidence: 99%
“…The peptide-based readouts in SPROX, LiP, PP, and DARTS provide structural information about the sites of ligand-induced conformational changes in proteins, whereas the protein-based readouts in TPP and CPP preclude the acquisition of such information. All of the above techniques have been widely used to identify the protein targets of drugs , and other biologically relevant molecules. ,,, It has been found that using more than one of the above proteomics methods for protein target discovery can reduce the false positive rate as overlapping hits are more likely to be true positives . Although these methods have been widely used in protein target elucidation studies, they have not been used to study structured RNA–protein interactions.…”
Section: Introductionmentioning
confidence: 99%